Production and characterization of hybrid briquettes from corncobs and oil palm trunk bark under a low pressure densification technique - Kpalo, Sunday Yusuf; Zainuddin, Mohamad Faiz; Abd Manaf, Latifah; Roslan, Ahmad Muhaimin (MDPI, 2020)
The objective of this research was to investigate the quality of hybrid briquettes developed from corncobs (CC) and oil palm trunk bark (OPTB) under a low-pressure densification technique. The materials were combined in varying ratios of CC to OPTB (100:0, 75:25, 50:50, 25:75, 0:100) and wastepaper pulp (10% by weight) was added to each mixture as a binder. The briquettes were produced using a manually operated 20-tonne hydraulic piston press at 28 °C temperature and ≤7 MPa compaction pressure. The mechanical strength of the briquettes was determined by the drop test and compression test methods, while a bomb calorimeter was used to determine the calorific values. The results showed that the physical properties of hybrid briquettes ranged from 9.24–10.00% moisture content, 0.38–0.40 g/cm3 density, and 87.60%–92.00% water resistance. Mechanical strength showed a 98.28%–99.08% shatter index and 18.47–21.75 MPa compressive strength, while calorific values ranged from 16.54–16.91 MJ/kg. The hybrid briquettes fared better than the CC briquettes. The significance of this study lies in the production of briquettes with suitable physical, mechanical and thermal properties by utilizing OPTB which have hitherto not been used, mixed with corncobs. This could bring substantial environmental and socio-economic benefits to rural communities of the developing countries.